Costs and economic indices of eucalyptus plantations from the Producer Forest Program in Espírito Santo State - Chichorro, Jose Franklim (2017)
Aiming to analyze timber production activity from the Producer Forest Program as an economic investment alternative, we collected data from eucalyptus plantations. We considered the costs of establishment, harvest and transportation separately. The costs of implantation and the price of wood (m³) were obtained from the company Fibria S.A. The harvesting and transportation costs were obtained from questionnaires applied in six properties in municipalities in the south of Espírito Santo State. All values of costs and prices were adjusted by the IPCA for 2014. The assessment includes an analysis of the costs for the production process, harvesting and transport and its participation in the total cost of the activity. It also includes the calculation of economic indicators of the activity as income gross, gross margin, net margin, profitability and rentability. The costs with greater participation in the production process were cost of land (34.91%), implantation (23.33%), transport (21.09%) and harvest (20.65%). According to the applied economic indices, the reforestation investment proved to be an economically viable alternative to producers, considering the obtained productivity and the wood price practiced by the company.